HUBUNGAN PENGETAHUAN DAN TINDAKAN PEMELIHARAAN KESEHATAN GIGI DAN MULUT DENGAN STATUS KESEHATAN GIGI PADA SISWA-SISWI SD GMIT PARITI KECAMATAN SULAMU KABUPATEN KUPANG - Ratu, Antonius R.; Manu, Apri A.; Wali, Agusthinus (SINERGI : Jurnal Riset Ilmiah, 2025)
The health status of teeth and mouth will affect a person's quality of life in interrelated domains, including symptoms of pain in the oral cavity, physical and psychological function, where oral function plays a very important role in supporting a person's health. Maintaining oral health is closely related to behavior and to change behavior requires the participation of the community where the individual lives. The closest environment in which individuals are located is the family environment and more broadly, namely the school environment. The knowledge and education provided by parents and teachers really helps shape children's behavior. Dental and oral health maintenance behavior can influence a person's dental health status. Efforts to maintain dental and oral health aim to prevent the occurrence of dental and oral diseases. Efforts to maintain dental and oral health that can support improving a person's health status include brushing teeth, gargling with fluoride solution, consuming foods that help keep teeth healthy and regular dental health checks. Objective: to determine the relationship between knowledge and health maintenance actions and dental health status in GMIT Pariti Elementary School students, Sulamu District, Kupang Regency Benefits: Can be used as a reference for improving the Dental Health Status of students through Method: This research uses an analytical survey method with a cross sectional study approach. The number of samples was 78 taken by total sampling. Data was taken through a questionnaire and data analysis using a correlation test with a significance value of p<0.05. The results of the research show that there is a relationship between knowledge and actions to maintain dental health and the dental health status of students in grades IV and V of SD GMIT Pariti, Sulamu District, Kupang Regency. (p-value 0.000 < 0.05). Conclusion: There is a relationship between knowledge and actions to maintain oral health and dental health status in students in grades IV and V at GMIT Pariti Elementary School, Sulamu District, Kupang Regency